Assessing the cost-effectiveness of electric vehicles in European countries using integrated modeling. (May 2015) - Seixas, J.; Simões, S.; Dias, L.; Kanudia, A.; Fortes, P.; Gargiulo, M.
Abstract: Electric vehicles (EVs) are considered alternatives to internal combustion engines due to their energy efficiency and contribution to CO2 mitigation. The adoption of EVs depends on consumer preferences, including cost, social status and driving habits, although it is agreed that current and expected costs play a major role. We use a partial equilibrium model that minimizes total energy system costs to assess whether EVs can be a cost-effective option for the consumers of each EU27 member state up to 2050, focusing on the impact of different vehicle investment costs and CO2 mitigation targets. We found that for an EU-wide greenhouse gas emission reduction cap of 40% and 70% by 2050 vis-à-vis 1990 emissions, battery electric vehicles (BEVs) are cost-effective in the EU only by 2030 and only if their costs are 30% lower than currently expected. At the EU level, vehicle costs and the capability to deliver both short- and long-distance mobility are the main drivers of BEV deployment. Other drivers include each state's national mobility patterns and the cost-effectiveness of alternative mitigation options, both in the transport sector, such as plug-in hybrid electric vehicles (PHEVs) or biofuels, and in other sectors, such as renewable electricity. Highlights: Electric vehicles were assessed through the minimization of the total energy systems costs. EU climate policy targets could act as a major driver for PHEV adoption. Battery EV is an option before 2030 if costs will drop by 30% from expected costs. EV deployment varies per country depending on each energy system configuration. Incentives at the country level should consider specific cost-effectiveness factors.